EVALUASI PELAKSANAAN PENGAWASAN PADA INSPEKTORAT KABUPATEN KUTAI KARTANEGARA TAHUN 2013 - Muriyanto . (Jurnal Paradigma (JP), 2017)
Evaluation is an activity collecting the information about the running program, furthermore the information used to decide the proper alternative in decision making process. This article is an effort to describe the process of evaluation in insprectorat department in Kutai Kartanegara.